Discovery of a second species in the genus Microlontha Petrovitz, 1967 (Coleoptera: Scarabaeidae: Rutelinae) - Uliana, Marco; Keith, Denis (Zootaxa, 2022)
A new species belonging to the poorly known genus Microlontha Petrovitz, 1967 is described from south-eastern Iran. Microlontha iranica Uliana & Keith, new species is different from the only other species of the genus chiefly for the strongly dentate margin of the clypeus and the color pattern.